PJMHS 2023
DOI: 10.53350/pjmhs2023171873
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Strain Counterstrain and Ischemic Compression Technique in Patients with Upper Trapezius Trigger Points

Abstract: Background: The trigger points are hyperirritable spots found usually in the muscle fascia or within the taut bands of skeletal muscles that is painful on compression. Ischemic compression technique uses the application of sustained pressure with sufficient force and for long enough so as to slow down the flow of blood and releasing tension out of the muscle. Strain counterstrain (SCS), also known as positional release, is a passive positional treatment that relieves musculoskeletal pain and dysfunction by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Setelah itu, otot upper trapezius dikembalikan ke posisi netral untuk menghindari re-excitation, sehingga membantu normalisasi tonus dan perpanjangan otot yang mengalami spasme atau kekakuan. 20 Metode energi otot dapat digunakan untuk memperpanjang otot dan meningkatkan rentang gerak sendi. Dua prinsip fisiologis yang mendasari MET adalah relaksasi post-isometrik (PIR) dan inhibisi resiprokal (RI).…”
Section: Pengaruh Kombinasi Us Dan Init Terhadap Perubahan Lingkup Ge...unclassified
“…Setelah itu, otot upper trapezius dikembalikan ke posisi netral untuk menghindari re-excitation, sehingga membantu normalisasi tonus dan perpanjangan otot yang mengalami spasme atau kekakuan. 20 Metode energi otot dapat digunakan untuk memperpanjang otot dan meningkatkan rentang gerak sendi. Dua prinsip fisiologis yang mendasari MET adalah relaksasi post-isometrik (PIR) dan inhibisi resiprokal (RI).…”
Section: Pengaruh Kombinasi Us Dan Init Terhadap Perubahan Lingkup Ge...unclassified
“…Various studies have demonstrated the efficacy of single interventions like cervical mobilization and PIR in addressing neck pain, cervical range of motion (ROM), and functional limitations linked to mechanically induced pain from MTrPs. [18–23] Limited studies have explored combined approaches, including manual techniques, deep friction massage, electrotherapy, or positional release, for managing MTrP-associated neck pain, ROM, and limitations. [24–27] However, the synergistic impact of cervical mobilization (CM) and PIR techniques remains unexplored in this context.…”
Section: Introductionmentioning
confidence: 99%